1992
DOI: 10.1007/bf00756787
|View full text |Cite
|
Sign up to set email alerts
|

Closed spaces in cosmology

Abstract: This paper deals with two aspects of relativistic cosmologies with closed (compact and boundless) spatial sections. These spacetimes are based on the theory of General Relativity, and admit a foliation into space sections ) (t S , which are spacelike hypersurfaces satisfying the postulate of the closure of space: each ) (t S is a 3-dimensional closed Riemannian manifold. The discussed topics are:(1) A comparison, previously obtained, between Thurston's geometries and Bianchi-Kantowski-Sachs metrics for such 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…The last two types are the Heisenberg group and the solvable Lie group. These types are anisotropic geometries and one can write an explicit metric for them [25]. However, it is not clear whether any of these last three types can be realized as a supersymmetric 3-cycle.…”
Section: Three Manifoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two types are the Heisenberg group and the solvable Lie group. These types are anisotropic geometries and one can write an explicit metric for them [25]. However, it is not clear whether any of these last three types can be realized as a supersymmetric 3-cycle.…”
Section: Three Manifoldsmentioning
confidence: 99%
“…In order to satisfy equation (25) with the boundary condition (36) ϕ has to approach a constant value in the far IR (r → ∞). Equation (37) then also requires e 2g to be asymptotically constant.…”
Section: Ads 2 × L Solutionsmentioning
confidence: 99%
“…D. Closed spaces in cosmology [9] This paper improves on the previous one, and discusses the question of local vs. global homogeneity of the constant curvature models.…”
Section: B Compactification Of Friedmann's Hyperbolicmentioning
confidence: 94%
“…where SL(2, R) is the universal covering of SL(2, R). In [45] it was shown that there exists a correspondence, not necessarily one to one, between the nine Bianchi cosmologies and the eight Thurston model geometries, which is summarized in table 1. 10 In the following, we list explicitely the metrics for solvegeometry/VI −1 and nilgeometry/II in terms of G-invariant one-forms θ A , as well as the nonvanishing structure constants of the related Lie algebras.…”
Section: Jhep12(2019)151mentioning
confidence: 99%